Alur Transmisi Kebijakan Moneter Ganda - Evi Nur Safitri; Islamiyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Monetary policy has a significant impact on the national economy by regulating money circulation and controlling the level of inflation in a country. In Indonesia there is a dual monetary system consisting of a conventional monetary system and an Islamic monetary system, of course there are differences between the two. So this research aims to understand how the dual monetary policy transmission flow operates in Indonesia, as well as the role of Islamic banks in the dual monetary policy transmission process. The research method used is literature study. So the results of this research show, although there are differences in the conventional and Islamic monetary systems, they are not much different, the difference lies in the principles and instruments used, the principles used in the Islamic monetary system are based on sharia economics. The role of Islamic banks in the transmission of dual monetary policy in Indonesia is very important, namely providing a positive impact on economic growth, this refers to the financing side through funding and sharia financing.